Analisis Soal Ujian Mata Pelajaran Ilmu Pengetahuan Alam Sekolah Dasar - Hartoyo Adi Saputro; Rini Rita T. Marpaung; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2018)
The aim of this study were to determine the quality and criteria of the subject of  School Exam Elementary. This research was qualitative research using documentation study. The subject of this study was the instrument of science school exam Elementary at School Year 2016/2017. The research instrument used assessment sheets and assessment rubrics. Data collection through documentation study by analyzing School Examination and Focus Group Discussion (FGD). Research data was analyzed descriptively qualitative. The results showed that most of the school exam questions (75%) were LOTS type while less than half (25%) were HOTS types. Characteristics of School Examination items type of stimulus was less than half of images, while a small portion were tables, examples, and fragments of cases. It was found that (97.5%) items were in accordance with indicators of achievement of competence.Penelitian bertujuan menentukan kualitas dan kriteria butir soal US IPA SD Tahun Ajaran 2016/2017. Penelitian ini merupakan penelitian kualitatif menggunakan studi dokumentasi. Subyek penelitian adalah instrumen soal US IPA SD Tahun Ajaran 2016/2017. Instrumen penelitian menggunakan lembar penilaian dan rubrik penilaian. Pengumpulan data melalui studi dokumentasi dengan menganalisis soal Ujian Sekolah dan Focus Group Discussion (FGD). Data penelitian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan soal ujian sekolah sebagian besar (75%) bertipe LOTS sedangkan kurang dari setengah (25%) bertipe HOTS. Karakteristik butir soal Ujian Sekolah pada jenis stimulus kurang dari setengahnya berupa gambar, sedangkan sebagian kecil berupa tabel, contoh, dan penggalan kasus. Ditemukan bahwa hampir semua (97,5%) butir soal sesuai dengan indikator pencapaian kompetensi.Kata kunci: HOTS, LOTS, kesesuaian, stimulus